2019
DOI: 10.3390/app9153106
|View full text |Cite
|
Sign up to set email alerts
|

Vision-Assisted Interactive Human-in-the-Loop Distal Upper Limb Rehabilitation Robot and its Clinical Usability Test

Abstract: In the context of stroke rehabilitation, simple structures and user-intent driven actuation are relevant features to facilitate neuroplasticity as well as deliver a sufficient number of repetitions during a single therapy session. A novel robotic treatment device for distal upper limb rehabilitation in stroke patients was developed, and a usability test was performed to assess its clinical feasibility. The rehabilitation robot was designed as a two-axis exoskeleton actuated by electric motors, consisting of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The lower computer and system status monitoring [23][24][25]. On the other hand, the operation of the lower computer software includes two aspects: on the one hand, it receives the control commands issued by the upper computer, and receives the connection code signal and the boundary switch to form a closed loop control [27][28].…”
Section: Upper Limb Rehabilitation Robot System Controlled By Internementioning
confidence: 99%
“…The lower computer and system status monitoring [23][24][25]. On the other hand, the operation of the lower computer software includes two aspects: on the one hand, it receives the control commands issued by the upper computer, and receives the connection code signal and the boundary switch to form a closed loop control [27][28].…”
Section: Upper Limb Rehabilitation Robot System Controlled By Internementioning
confidence: 99%
“…In this sense, integrating usability evaluation during the development of rehabilitation technologies was shown to contribute to device design improvements, user satisfaction and device usability (Shah and Robinson, 2007;Power et al, 2018;Meyer et al, 2019). Unfortunately, the usability of robotic devices for upper-limb rehabilitation is only rarely evaluated and documented in the target user population before clinical tests (Pei et al, 2017;Catalan et al, 2018;Guneysu Ozgur et al, 2018;Nam et al, 2019;Tsai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ad hoc questionnaires. Reported by six of the selected studies [30][31][32][33][34][35], this type of instrument was most often reported without any evaluation of the dimensionality nor validity nor reliability, as well as with any description of scoring procedures. Therefore, this method was assigned a mean score of 5 out of 17 in our critical appraisal checklist.…”
Section: Quantitative and Subjective Assessment Methods Of Usability In The Use Of Rehabilitative Exoskeletonsmentioning
confidence: 99%